CRISIS COMMUNICATION ON X: AQUA’S RESPONSE TO BOYCOTT ALLEGATIONS OVER THE ISRAEL–PALESTINE CONFLICT - Pasaribu, Samsul Bahri; P, Indira Fatra Deni (Pena Cendekia Insani, 2025)
This study aims to analyze the crisis communication strategy of the X account @SehatAQUA in responding to the boycott issue triggered by the Israel–Palestine geopolitical controversy. The research applies the Situational Crisis Communication Theory (SCCT) as a theoretical framework, using a qualitative case study approach. Observations were conducted on the @SehatAQUA account from March 24 to 29, 2025. The primary data analyzed consisted of 14 items: 5 negative public responses, 5 positive public responses, and 4 official posts or press releases from Aqua. Secondary data from news coverage and academic literature were used to strengthen the contextual interpretation. Data validity was ensured through source triangulation. The findings reveal that Aqua adopted a rebuild posture strategy as outlined in SCCT by delivering transparent clarifications, affirming political neutrality, debunking disinformation with UN-based data, collaborating with mainstream media, and promoting digital literacy. This strategy proved effective in shifting public sentiment from negative to more positive and reinforcing a humanitarian-based brand image. The study highlights the importance of a timely, data-driven, and values-oriented crisis communication response in addressing geopolitical pressure in the digital age.